NADPH Oxidase 4 Mediates Monocyte Priming and Accelerated Chemotaxis Induced by Metabolic Stress - Ullevig, Sarah (2011)
OBJECTIVE: Metabolic disorders increase MCP-1-induced monocyte chemotaxis in mice. The goal of this study was to determine the molecular mechanisms responsible for the enhanced responsiveness of monocytes to chemoattractants induced by metabolic stress. METHODS AND RESULTS: Chronic exposure of monocytes to diabetic conditions induced by human low-density lipoproteins plus high D-glucose concentrations (LDL+HG) promoted Nox4 expression, increased intracellular H(2)O(2) formation, stimulated protein S-glutathionylation, and increased chemotaxis in response to MCP-1, PDGF-B and RANTES. Both, H(2)O(2) added exogenously and overexpression of Nox4 mimicked LDL+HG-induced monocyte priming, whereas Nox4 knockdown protected monocytes against metabolic stress-induced priming and accelerated chemotaxis. Exposure of monocytes to LDL+HG promoted the S-glutathionylation of actin, decreased the F-actin/G-actin ratio and increased actin remodeling in response to MCP-1. Preventing LDL+HG-induced protein S-glutathionylation by overexpressing glutaredoxin 1 (Grx1) prevented monocyte priming and normalized monocyte chemotaxis in response to MCP-1. Induction of hypercholesterolemia and hyperglycemia in C57BL/6 mice promoted Nox4 expression and protein-S-glutathionylation in macrophages, and increased macrophage recruitment into MCP-1-loaded Matrigel plugs implanted subcutaneous in these mice. CONCLUSIONS: By increasing actin-S-glutathionylation and remodeling, metabolic stress primes monocytes for chemoattractant-induced transmigration and recruitment to sites of vascular injury. This Nox4-dependent process provides a novel mechanism through which metabolic disorders promote atherogenesis.